Low concentration contrast medium for dual-source computed tomography coronary angiography by a combination of iterative reconstruction and low-tube-voltage technique: Feasibility study - Zheng, Minwen; Liu, Ying; Wei, Mengqi; Wu, Yongjie; Zhao, Hongliang; Li, Jian (European journal of radiology, 2014)
To assess the impact of low-concentration contrast medium on vascular enhancement, image quality and radiation dose of coronary CT angiography (cCTA) by using a combination of iterative reconstruction (IR) and low-tube-voltage technique. One hundred patients were prospectively randomized to two types of contrast medium and underwent prospective electrocardiogram-triggering cCTA (Definition Flash, Siemens Healthcare; collimation: 128mm×0.6mm; tube current: 300mAs). Fifty patients received Iopromide 370 were scanned using the conventional tube setting (100kVp or 120kVp if BMI≥25kg/m2) and reconstructed with filtered back projection (FBP). Fifty patients received Iodixanol 270 were scanned using the low-tube-voltage (80kVp or 100kVp if BMI≥25kg/m2) technique and reconstructed with IR. CT attenuation was measured in coronary artery and other anatomical regions. Noise, image quality and radiation dose were compared. Compared with two Iopromide 370 subgroups, Iomeprol 270 subgroups showed no significant difference in CT attenuation (576.63±95.50 vs. 569.51±118.93 for BMI<25kg/m2, p=0.647 and 394.19±68.09 vs. 383.72±63.11 for BMI≥25kg/m2, p=0.212), noise (in various anatomical regions of interest) and image quality (3.5 vs. 4.0, p=0.13), but significantly (0.41±0.17 vs. 0.94±0.45 for BMI<25kg/m2, p<0.001 and 1.14±0.24 vs. 2.37±0.69 for BMI≥25kg/m2, p<0.001) lower radiation dose, which reflects dose saving of 56.4% and 51.9%, respectively. Combined IR with low-tube-voltage technique, a low-concentration contrast medium of 270mgI/ml can still maintain the contrast enhancement without impairing image quality, as well as significantly lower the radiation dose.